Use of epoxy-phenolic lacquers in food can coatings: Characterization of lacquers and cured films - Manfredi, Liliana Beatriz (2005)
Liquid and cured epoxy-phenolic lacquers used as can coatings were characterized. Tinplate was used as the base material, which was coated with lacquers of different epoxy to phenolic ratios (EPRs) from a commercial source. Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), and thermogravimetric analysis (TGA) were used together to obtain helpful information about the degree of curing and the composition of the lacquers. From FTIR analysis, we were able to infer that the lacquers were composed of a high-molecular-weight diglycidyl ether of bisphenol A type epoxy resin and a resol-type phenolic resin. In addition, from FTIR spectra, we estimated the EPRs of lacquers applied on the tinplate and detected if they had been overcured. The EPRs of the applied lacquers were estimated also from DSC analysis. From TGA, we detected undercuring in the applied lacquers. © 2005 Wiley Periodicals, Inc.